Reference and Bibliographic Service: Going Beyond the Classical Model - M. Yu. Neshcheret (Библиосфера, 2023)
The article gives a brief description of present reference and bibliographic service models. Its aim is to show the tendencies of reference and bibliographic services development under the conditions of information (and later – digital) technologies. Tracing the evolution of reference and bibliographic services in the aspect of expanding the range of information services the author comes to the conclusion that during the introduction of information technologies, there has appeared a tendency to integrate various types of information services and, as a result, to put out reference and bibliographic services beyond the classical model. Thus, it requires its adjustment taking into account the information needs of new generation users. It is assumed that thanks to the increase in the capacity of the service resource base, the range of comprehensive information services of a research nature aimed at broad information science support, as well as creative and business activities, will expand.